An Investigation of Lower Limb Representations Underlying Vision, Touch, and Proprioception in Body Integrity Identity Disorder - Stone, Kayla D.; Kornblad, Clara A. E.; Engel, Manja M.; Dijkerman, H. Chris; Blom, Rianne M.; Keizer, Anouk (Frontiers in Psychiatry, 2020)
Individuals with Body Integrity Identity Disorder (BIID) have a (non-psychotic) longstanding desire to amputate or paralyze one or more fully-functioning limbs, often the legs. This desire presumably arises from experiencing a mismatch between one’s perceived mental image of the body and the physical structural and/or functional boundaries of the body itself. While neuroimaging studies suggest a disturbed body representation network in individuals with BIID, few behavioural studies have looked at the manifestation of this disrupted lower limb representations in this population. Specifically, people with BIID feel like they are overcomplete in their current body. Perhaps sensory input, processed normally on and about the limb, cannot communicate with a higher-order model of the leg in the brain (which might be underdeveloped). We asked individuals who desire paralysis or amputation of the lower legs (and a group of age- and sex-matched controls) to make explicit and implicit judgements about the size and shape of their legs while relying on vision, touch, and proprioception. We hypothesized that BIID participants would mis-estimate the size of their affected leg(s) more than the same leg of controls. Using a multiple single-case analysis, we found no global differences in lower limb representations between BIID participants and controls. Thus, while people with BIID feel that part of the body is foreign, they can still make normal sensory-guided implicit and explicit judgements about the limb. Moreover, these results suggest that BIID is not a body image disorder, per se, and that an examination of leg representation does not uncover the disturbed bodily experience that individuals with BIID have.